Offshore wind turbine foundation monitoring, extrapolating fatigue measurements from fleet leaders to the entire wind farm. Issue 9 (September 2016) - Weijtens, Wout; Noppe, Nymfa; Verbelen, Tim; Iliopoulos, Alexandros; Devriendt, Christof
Abstract: The present contribution is part of the ongoing development of a fatigue assessment strategy driven purely on in-situ measurements on operational wind turbines. The primary objective is to estimate the remaining life time of existing wind farms and individual turbines by instrumenting part of the farm with a load monitoring setup. This load monitoring setup allows to measure interface loads and local stress histories. This contribution will briefly discuss how these load measurements can be translated into fatigue assessment of the instrumented turbine. However, due to different conditions at the wind farm, such as turbulence, differences in water depth and foundation design this turbine will not be fully representable for all turbines in the farm. In this paper we will use the load measurements on two offshore wind turbines in the Northwind offshore wind farm to discuss fatigue progression in an operational wind farm. By calculating the damage equivalent loads on the two turbines the fatigue progression is quantified for every 10 minute interval and can be analyzed against turbulence and site conditions. In future work these results will be used to predict the fatigue life progression in the entire farm.